Determination of a psychophysiological state of aviations operators - Ударцева, Т.Є. (Proceedings of National Aviation University (archive), 2004)
The results of a complex research of a functional state of the members of crew’s airs liners before and after execution of the job on a training simulator Яk-40 are considered. The probability statistical approach to an evaluation of dynamics of psychophysiologicals states is offered probability.